2020
DOI: 10.1101/2020.07.08.194076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Several geranylgeranyl diphosphate synthase isoforms supply metabolic substrates for carotenoid biosynthesis in tomato

Abstract: ABSTRACTGeranylgeranyl diphosphate (GGPP) produced by GGPP synthase (GGPPS) serves as a precursor for many plastidial isoprenoids, including carotenoids. Here we show that five different GGPPS isoforms exist in tomato (Solanum lycopersicum). From these, SlGGPPS1, 2 and 3 (or SlG1-3 in short) produce GGPP in plastids and exhibit similar kinetic parameters. Phytoene synthase (PSY) converts GGPP into phytoene, the first committed intermediate of the caro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The expression of PSY1 is boosted during the ripening process, thereby promoting the generation of carotenoids that contribute to fruit pigmentation (Kachanovsky et al, 2012). Previous studies have found that unlike other plants such as Arabidopsis, rice or pepper, which rely on a single GGPPS isoform for the production of the required plastid-like isoprenoids, the production of a majority of the GGPP in the chloroplasts of tomato is dependent on two GGPPS homologues (Zhou et al, 2017;Wang et al, 2018;Barja et al, 2021). Their experiments also confirmed that PSY1 expression was significantly increased in fruit ripening.…”
Section: Slnap2 Influences Chlorophyll and Carotenoid Metabolism In T...mentioning
confidence: 99%
“…The expression of PSY1 is boosted during the ripening process, thereby promoting the generation of carotenoids that contribute to fruit pigmentation (Kachanovsky et al, 2012). Previous studies have found that unlike other plants such as Arabidopsis, rice or pepper, which rely on a single GGPPS isoform for the production of the required plastid-like isoprenoids, the production of a majority of the GGPP in the chloroplasts of tomato is dependent on two GGPPS homologues (Zhou et al, 2017;Wang et al, 2018;Barja et al, 2021). Their experiments also confirmed that PSY1 expression was significantly increased in fruit ripening.…”
Section: Slnap2 Influences Chlorophyll and Carotenoid Metabolism In T...mentioning
confidence: 99%